Experimental and numerical investigation of low-pressure laminar premixed synthetic natural gas flames in rich conditions. (1st February 2017) - Lefort, B.; El Bakali, A.; Gasnot, L.; Pauwels, J.F.
Highlights: Low-pressure laminar premixed flames of natural gas were realized in rich conditions. A detailed mechanism was developed and validated against different experimental conditions. One focus of the study is to explain the formation of single ring in our conditions. Abstract: The present work concerns the study of rich laminar premixed CH4 /C2 H6 /C3 H8 /O2 /N2 flames operating at two equivalence ratios (ϕ = 1.66 and 2.05) and low pressure (80 Torr). In the case of the flame ϕ = 2.05, the influence of pressure was studied between 80 and 300 Torr. Mole fraction of reactants, stable intermediate and combustion products have been obtained using a quartz microprobe coupled to gas chromatography, mass spectrometry and infrared spectroscopy technique analysis. Temperature profiles measured with a coated thermocouple were corrected from radiative heat losses by electrical compensation method. A detailed chemical kinetic mechanism has been developed. Globally the main experimental observations are well captured by the present mechanism, especially the effect of the equivalence ratio and pressure on the chemical species distribution. The proposed mechanism has been also tested to predict detailed and global data in other experimental conditions (ignition delay times, burning velocities, and jet stirred reactor). Reactions paths analyses have been carried out to identify the main reactions routes governing natural gas combustion in rich conditions. Both effect of pressure and initial composition on C2 (ethylene, acetylene), C3 (allene, propyne) and C4 (butadiene, butyne) hydrocarbon species known as first ring precursors, have been examined. It was observed that self propargyl radicals is the main reaction route determining benzene formation in natural gas combustion in rich conditions.